Objective and Subjective Cognitive Decline in Patients with Testicular Cancer after Treatment: A systematic review - Karlíková, Bianka; Uhrecký, Branislav; Gurňáková, Jitka (Archives of Men’s Health, 2023)
Introduction: Patients with testicular cancer can live for several decades with completed treatment. Because of the availability of treatment, increasing attention is paid to its toxicity, which has adverse effects on physical, emotional, and cognitive functions. The results so far suggest that chemotherapy is responsible for multiple cognitive failures. On the other hand, the ambivalence of the results is shown by subjectively reported cognitive disorders, which are more frequent than in objective testing. This paper aims to review the literature and to identify and investigate the prevalence of affected domains, and the correlates of subjective and objective cognitive impairment in men treated for testicular cancer. Methods: Scopus, Web of Science, EBSCO (MEDLINE, PsycINFO, Psychology and Behavioral Sciences Complete), and PubMed were searched for articles written in the English language that focused on objective and subjective cognitive difficulties in patients with testicular cancer with different types of oncological treatment. The PRISMA system was used to review the articles and ensure methodological accuracy. Of the 432 scientific articles, 24 articles were included in the systematic analysis. Results: Most articles used a quantitative (n = 20) or mixed-methods design (n = 4). Using 10 articles with objective tests and 9 articles with subjectively perceived decline, cognitive difficulties were present in patients after surgical treatment and chemotherapy and at different time horizons compared with the healthy population. Most results were related to difficulties after chemotherapy, type of chemotherapy, and number of completed cycles. Subjectively perceived difficulties did not correlate with the results of objective tests, and the results were more related to experienced fatigue, emotional stress, etc. Conclusion: Further research is needed to provide a more comprehensive view of the cognitive difficulties of testicular cancer patients and to develop a consistent battery of tests and scales.